Preparation method of copper-based deep desulfurizing agent
By adopting the preparation method of copper-based deep desulfurization agent, copper oxide products with β-CuO crystal form are generated and mixed with other additives, the problem of insufficient precision desulfurization in the existing technology is solved, the desulfurization accuracy and the service life of the catalyst are significantly improved, and economic and environmental benefits are improved.
Patent Information
- Application Number
- CN202411968891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art cannot further improve the accuracy of refined desulfurization in coke oven gas production and LNG processes, resulting in insufficient service life of methanol synthesis catalysts and methanation catalysts, affecting economic and environmental benefits.
A copper-based deep desulfurization agent is used to prepare a copper-based deep desulfurization agent. By dissolving soluble copper salt in water, adding an alkaline precipitant and reacting under specific pH and temperature conditions, a β-CuO crystalline copper oxide product is generated, and mixed with ammonium molybdate, zinc oxide powder and guar gum. After steam curing and drying, the desulfurization accuracy and product strength are improved.
It significantly improves the desulfurization accuracy from 0.03ppm to 0.005ppm, extends the service life of the catalyst, improves the economic and environmental benefits of the enterprise, and enhances the water resistance and strength of the product.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a copper-based deep desulfurizing agent, and belongs to the field of desulfurized gas purification. Background Art
[0002] At present, in the domestic coal chemical industry, especially in the coke oven gas to methanol and coke oven gas to LNG processes, in order to protect the expensive methanol synthesis catalyst and methanation catalyst, it is necessary to remove the total sulfur to the lowest possible level in the previous fine desulfurization process to prevent the methanol synthesis catalyst and methanation catalyst from sulfur poisoning, which would affect their methanol synthesis activity or methanation activity.
[0003] Fine desulfurization can significantly reduce the sulfur content in coke oven gas. Since sulfur is a harmful impurity in methanol, excessive content will seriously affect the purity and stability of methanol. Through fine desulfurization technology, the sulfur in coke oven gas is effectively removed, thereby ensuring that the produced methanol has high purity and meets the market demand for high-quality methanol. Sulfides in coke oven gas, including H2S, COS, CS2, etc., are also highly toxic to methanation catalysts. If these sulfides enter the methanation reactor without treatment, they will react with the active components of the catalyst, causing the catalyst to be deactivated, seriously affecting the methanation reaction. Therefore, fine desulfurization is also an indispensable link in the coke oven gas to LNG process. Its primary function is to protect the methanation catalyst from the poisoning of sulfides and ensure that the methanation reaction can be carried out efficiently and stably. At the same time, sulfides are corrosive. If the sulfide content in coke oven gas is too high, it will cause serious corrosion problems to the process equipment. This will not only affect the normal operation and service life of the equipment, but may also cause safety accidents. Through fine desulfurization treatment, the sulfide content in coke oven gas can be reduced, thereby reducing the corrosion risk of equipment and ensuring the safe and stable operation of the process. Sulfur will produce harmful gases such as sulfur dioxide during the combustion process, which will pollute the environment. Through fine desulfurization, the emission of harmful gases can be reduced, the pollution to the environment can be reduced, the degree of corrosion of equipment can be reduced, the service life of equipment can be extended, and the maintenance cost of the enterprise can be reduced. In summary, the effects of fine desulfurization in the production of methanol from coke oven gas include improving the quality of methanol / LNG, protecting methanol synthesis catalyst / methanation catalyst, and reducing equipment corrosion and environmental pollution. These effects together provide important support for coking enterprises to improve economic benefits and market competitiveness.
[0004] At present, the fine desulfurization in the methanol synthesis scenario generally removes the total sulfur to below 0.1ppm, while the fine desulfurization in the methanation catalyst scenario generally removes the total sulfur to below 0.03~0.05ppm. As the market's requirements for economic benefits increase, the requirements for the life of methanol synthesis catalysts and methanation catalysts also increase, and the removal accuracy of fine desulfurization must be further improved. The present invention is produced under this background. Summary of the invention
[0005] The present invention mainly solves the problem of fine desulfurization accuracy of coke oven gas to methanol and LNG products, so as to further extend the service life of methanol synthesis catalyst and methanation catalyst, and improve the economic and environmental benefits of enterprises. The present invention provides a method for preparing a copper-based deep desulfurizer for coke oven gas fine desulfurization with a simple manufacturing process.
[0006] In order to solve the above technical problems, the present invention relates to a method for preparing a copper-based deep desulfurization agent, and the preparation method comprises the following steps: (a) dissolving a soluble copper salt, such as copper sulfate pentahydrate, copper nitrate or copper chloride, in water to obtain a solution A; (b) dissolving an alkaline precipitant, one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate, in water to obtain solution B, and mixing and stirring the solution A obtained in step (a) in a stirred tank at a certain molar ratio of alkaline ions to copper ions to fully react, wherein the molar ratio here needs to ensure that the copper ions are completely precipitated. If the anion of the precipitant is hydroxide, the molar ratio of hydroxide to copper ions is 2:1; if the anion of the precipitant is carbonate, the molar ratio of hydroxide to copper ions is 1:1; (c) The slurry obtained in step (b) is further added with solution B prepared in the same way until the pH is alkaline between 7.0 and 9.5, and heated to 55-70°C to allow the reaction to continue. Under this pH and temperature condition, β-CuO crystal can be obtained, and its lattice constant is twice that of the common α-CuO, belonging to the tetragonal system. In terms of desulfurization performance, a higher desulfurization accuracy can be obtained than that of α-CuO products; (d) filtering, washing and drying the slurry obtained in step (c) to obtain solid C, and then roasting to obtain solid D; (e) taking a portion of the product obtained in step (d) and mixing it evenly with ammonium molybdate, zinc oxide powder and guar gum in a certain proportion of 30%:7%:60%:3%, and then adding water to extrude the product into strips, wherein the addition of ammonium molybdate can make the product have higher strength; (f) The product obtained in (e) is steam-cured in a closed reactor in a 120° C. steam environment generated by heated water for 3 hours, and then dried at 130° C. This curing process can allow the product to obtain better water resistance.
[0007] The present invention has the following advantages: (1) The copper-based deep desulfurizer prepared by the present invention can obtain a β-CuO crystal-type copper oxide product after a reaction at a specific pH value and a characteristic temperature, and its lattice constant is about twice as high as that of the usual α-CuO lattice constant. The doubled lattice constant allows the copper-based deep desulfurizer of the present invention to obtain better desulfurization activity. The desulfurization accuracy is increased from 0.03ppm to 0.005ppm.
[0008] (2) Mixing the obtained copper oxide solid with ammonium molybdate can make the product have higher strength, which is increased by about 30%, allowing the product to withstand more friction impact and higher air speed without breaking.
[0009] (3) The mixed extruded products can be cured with 120°C steam generated by heating water in a closed reactor to obtain better water resistance, which can reduce the problem of powderization of such products when exposed to water during industrial use. DETAILED DESCRIPTION Example 1
[0010] An aqueous solution of 250 g of copper sulfate pentahydrate dissolved in water and an aqueous solution of 80 g of sodium hydroxide dissolved in water are uniformly mixed and fully stirred, with a molar ratio of hydroxide to copper ion of 2:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the pH value of the solution to 7.0, and the solution is heated to 55° C. and reacted for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150° C. After drying, 30 g of the calcined copper oxide solid is mixed with 7 g of ammonium molybdate, 60 g of zinc oxide, and 3 g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120° C. steam after heating water for 3 hours, and then dried at 130° C. for 2 hours, to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0011] The desulfurizer has been evaluated and found to have a strength of 170N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 2
[0012] An aqueous solution of 250 g of copper sulfate pentahydrate dissolved in water and an aqueous solution of 80 g of sodium hydroxide dissolved in water are uniformly mixed and fully stirred, with a molar ratio of hydroxide to copper ion of 2:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 9.5, and the solution is heated to 70°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30 g of the calcined copper oxide solid is taken after drying and mixed with 7 g of ammonium molybdate, 60 g of zinc oxide, and 3 g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0013] The desulfurizer has been evaluated and found to have a strength of 173N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 3
[0014] 250g of an aqueous solution of copper sulfate pentahydrate dissolved in water and 80g of an aqueous solution of sodium hydroxide dissolved in water are uniformly mixed and fully stirred, and the molar ratio of hydroxide to copper ion is 2:1. The reaction is carried out for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out from the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude, and the extruded sample is cured in a closed reactor with 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0015] The desulfurizer has been evaluated and found to have a strength of 171N / cm, an α-CuO crystal structure, a desulfurization accuracy of 0.03ppm, and will not turn into powder after being soaked in water for 24 hours. Example 4
[0016] An aqueous solution of 250g of copper nitrate dissolved in water and an aqueous solution of 112g of potassium hydroxide dissolved in water are uniformly mixed and fully stirred, with a molar ratio of hydroxide to copper ion of 2:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 8.0, and the solution is heated to 65°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0017] The desulfurizer has been evaluated and found to have a strength of 172N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 5
[0018] An aqueous solution of 250g of copper nitrate dissolved in water and an aqueous solution of 112g of potassium hydroxide dissolved in water are uniformly mixed and fully stirred, with a molar ratio of hydroxide to copper ion of 2:1, and then a sodium hydroxide solution of the same concentration is added to adjust the pH value of the solution to 8.0, and the solution is heated to 65°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 60g of zinc oxide and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0019] The desulfurizer has been evaluated and found to have a strength of 130N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 6
[0020] An aqueous solution of 188g of copper nitrate dissolved in water and an aqueous solution of 106g of sodium carbonate dissolved in water are uniformly mixed and fully stirred, with a molar ratio of carbonate to copper ion of 1:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 7.0, and the solution is heated to 55°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0021] The desulfurizer has been evaluated and found to have a strength of 175N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 7
[0022] An aqueous solution of 188g of copper nitrate dissolved in water and an aqueous solution of 106g of sodium carbonate dissolved in water are uniformly mixed and fully stirred, with a molar ratio of carbonate to copper ion of 1:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 7.0, and the solution is heated to 55°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extruded strips, and the extruded sample is cured in a closed reactor with 90-100°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0023] The desulfurizer has been evaluated and found to have a strength of 170N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will turn into powder after being soaked in water for 24 hours. Example 8
[0024] An aqueous solution of 188g of copper nitrate dissolved in water and an aqueous solution of 138g of potassium carbonate dissolved in water are uniformly mixed and fully stirred, with a molar ratio of carbonate to copper ion of 1:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 7.0, and the solution is heated to 55°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out from the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0025] The desulfurizer has been evaluated and found to have a strength of 173N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 9
[0026] An aqueous solution of 135g of copper chloride dissolved in water and an aqueous solution of 138g of potassium carbonate dissolved in water are uniformly mixed and fully stirred, with a molar ratio of carbonate to copper ion of 1:1, and then a separately prepared sodium hydroxide solution of the same concentration is added to adjust the solution pH to 9.0, and the solution is heated to 65°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0027] The desulfurizer has been evaluated and found to have a strength of 171N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours. Example 10
[0028] An aqueous solution of 135g of copper chloride dissolved in water and an aqueous solution of 80g of sodium hydroxide dissolved in water are uniformly mixed and fully stirred, with a molar ratio of carbonate to copper ion of 1:1, and then a sodium hydroxide solution of the same concentration is added to adjust the pH value of the solution to 9.5, and the solution is heated to 70°C for reaction for 3 hours to obtain a slurry containing active copper oxide precipitate, and the precipitate is filtered out of the obtained slurry, and the precipitate is washed and dried at 150°C, and 30g of the calcined copper oxide solid is taken after drying and mixed with 7g of ammonium molybdate, 60g of zinc oxide, and 3g of guar gum to extrude strips, and the extruded sample is cured in a closed reactor under 120°C steam after heating water for 3 hours, and then dried at 130°C for 2 hours, so as to obtain the preparation method of the copper-based deep desulfurizer of the present invention.
[0029] The desulfurizer has been evaluated and found to have a strength of 174N / cm, a β-CuO crystal structure, a desulfurization accuracy of 0.005ppm, and will not turn into powder after being soaked in water for 24 hours.
[0030] Table 1 Physical indicators and sulfur capacity of the preparation method of copper-based deep desulfurizer compared with control variables project Variable comparison Product Strength Desulfurization accuracy 24h water resistance Example 1 The solution was adjusted to pH 7.0 and the temperature was 55°C. 170N / cm 0.005ppm Not powdered Example 2 The solution was adjusted to pH 9.5 and temperature 70°C 173N / cm 0.005ppm Not powdered Example 3 Unconditioned pH and temperature 171N / cm 0.030ppm Not powdered Example 4 Add ammonium molybdate 172N / cm 0.005ppm Not powdered Example 5 Without ammonium molybdate 130N / cm 0.005ppm Not powdered Example 6 120℃ steam curing 175N / cm 0.005ppm Not powdered Example 7 90~100℃ steam curing 170N / cm 0.005ppm Powdering ① From the comparison of Example 1, Example 2 and Example 3 in Table 1, it can be seen that when the pH value of the solution is adjusted to between 7 and 9.5 and the solution temperature is between 55 and 70°C (Examples 1 and 2), the produced copper oxide crystal form is β-CuO, and the lattice constant is much higher than that of α-CuO in Example 3, and the desulfurization accuracy is also significantly improved, from 0.03ppm to 0.005ppm.
[0031] ② It can be seen from Example 4 and Example 5 in Table 1 that when ammonium molybdate is added, the product strength is increased by about 30%.
[0032] ③ It can be seen from Example 6 and Example 7 in Table 1 that under steam curing at 120°C in a closed reactor, the product has better water resistance than steam curing at 90-100°C, and can be immersed in water for 24 hours without powdering.
[0033] In the above-mentioned embodiments 1 to 10, the water used is deionized water, cupric sulfate pentahydrate is an analytical reagent with a purity of 99.8%, cupric chloride is an analytical reagent with a purity of 99%, cupric nitrate is an analytical reagent with a purity of 99%, sodium hydroxide is an analytical reagent with a purity of 99%, potassium hydroxide is an analytical reagent with a purity of 99%, sodium carbonate is an analytical reagent with a purity of 99%, potassium carbonate is an analytical reagent with a purity of 99%, ammonium molybdate is an analytical reagent with a purity of 99%, zinc oxide powder is 99.99% high-purity zinc oxide powder, and guar gum is an industrial-grade product with a purity of 99%. Extrusion is carried out on a twin-screw extruder, high-temperature steam curing is carried out in a reactor, drying is carried out in an electric hot air drying oven, and roasting is carried out in an electric roasting furnace.
[0034] Although the present invention has described the above multiple implementation cases in detail, those skilled in the art should understand that any changes in form and details made on this basis are within the scope of protection of the present invention.
Claims
1. A method for preparing a copper-based deep desulfurizing agent, characterized in that The steps include: (a) dissolving a soluble copper salt in water to obtain a solution A; (b) dissolving the alkaline precipitant in water to obtain solution B and mixing the solution B with the solution A obtained in step (a) in a stirred tank at a certain molar ratio to achieve sufficient reaction; (c) Adding solution B prepared in the same manner to the slurry obtained in step (b) until the pH is alkaline, and heating to 55-70° C. to allow the reaction to continue; (d) filtering, washing and drying the slurry obtained in step (c) to obtain solid C, and then roasting to obtain solid D; (e) adding ammonium molybdate, zinc oxide powder, adhesive and water to a portion of the product D obtained in step (d) in a certain proportion, mixing the mixture evenly, and then extruding the mixture into strips; (f) The product obtained in (e) was steam cured for 3 hours in a closed reaction vessel using 120°C steam generated by heating, and then dried at 130°C.
2. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: The soluble copper salt is one of copper sulfate pentahydrate, copper nitrate and copper chloride.
3. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: The alkaline precipitant in step (b) is one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
4. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: In step (c), the pH value is between 7.0 and 9.5, and the solution temperature is between 55 and 70°C.
5. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: In step (e), the proportions of the solid, molybdenum acid, zinc oxide powder and adhesive are 30%, 7%, 60% and 3% respectively.
6. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: The adhesive in step (e) is guar gum.
7. The method for preparing a copper-based deep desulfurizing agent according to claim 1, characterized in that: The steam curing in step (f) uses steam at 120° C. generated by heating water in a closed reactor.